The role of intermittent fasting diet in NAFLD management: A scoping review of RCT and clinical trial studies in adult patients - Adilah Robbaniyah; Dian Handayani (AcTion: Aceh Nutrition Journal, 2025)
Non-Alcoholic Fatty Liver Disease (NAFLD) is the accumulation of fat in the liver not caused by alcohol consumption and is now a leading cause of chronic liver disease globally. Intermittent fasting has the potential to improve the metabolic parameters associated with NAFLD; however, more scientific evidence is needed to confirm this. This review aims to examine the role of intermittent fasting in the management of NAFLD based on existing research. The method used was A scoping review was conducted with a literature search through the PubMed and ScienceDirect databases, and article selection was performed using the PRISMA flow. The inclusion criteria were randomized controlled trials (RCTs) or clinical trials published between 2014 and 2024, resulting in seven articles meeting the criteria. The results showed that various IF methods, such as 5:2 fasting, Alternate-Day Fasting and Time-Restricted Eating, can reduce body weight, waist circumference, fat mass, and several biochemical parameters, such as triglycerides, LDL, total cholesterol, ALT, AST, and inflammatory markers. However, its effectiveness on biochemical parameters still requires further study due to the limited number of studies that comprehensively address these parameters. In conclusion, IF is considered safe for patients with NAFLD and may be a strategic approach to improve NAFLD.